Tube-Cornea Touch Following an Ahmed Valve Implantation in a Patient with Congenital Rubella Syndrome: A Case Report. - Ooi, Edwin IL; Safinaz MK,; Ropilah AR, (Department of Surgery, UKM Medical Centre, 2014)
This was a 28-year-old mentally-challenged girl with underlying congenital Rubella syndrome. She was bilaterally aphakic after congenital cataract surgery. She then developed bilateral aphakic glaucoma and had to undergo multiple glaucoma filtering surgeries. The most recent procedure she had undergone for her left eye was a second Ahmed valve implantation with an overlying sclera patch. Postoperatively, intraocular pressure was well controlled. However, nine months later, slit lamp examination revealed the tube was adherent to the overlying cornea with surrounding deep and superficial cornea vascularization. Siedel test was negative and intraocular pressure was normal. Subsequently the tube was removed but the plate was left in situ.